Assessing morphological characteristics of elite cotton lines from different breeding programmes for low temperature and drought tolerance. (26th March 2018) - Singh, B.; Norvell, E.; Wijewardana, C.; Wallace, T.; Chastain, D.; Reddy, K. R.
Abstract: Cotton breeders in the United States strive to develop region‐specific genotypes adapted to low temperatures and variable soil moistures during early‐season planting. Nine elite upland cotton germplasm ( Gossypium hirsutum L.) lines, representing public breeding programmes from nine states across the cotton belt, were evaluated for cold and drought stresses during seed germination and seedling growth stages. Lines were subjected to three treatments, such as low temperature well‐watered (22/14°C, WW), optimal temperature drought stress (30/22°C, DS) and optimal temperature well‐watered (30/22°C, WW; control), to examine genotypic variability for cold and drought tolerance. The treatment including drought stress was irrigated at 50% of the control. Shoot and root traits measured at 25 days after planting were significantly affected by drought and low temperature, where significant genetic variability among lines was observed for both shoot and root parameters. Response indices were developed to quantify variation in the degree of tolerance among the lines to low temperature and drought. Accordingly, OA‐33 was identified as the most low‐temperature‐tolerant line and Acala 1517‐99 as the most drought‐tolerant line. Identification of both cold‐ and drought‐tolerant genotypes suggests existing genotypic variability could provide breeders the opportunity to improve cultivar response to early‐season drought or cold conditions.